Vibratory synchronization transmission of a cylindrical roller in a vibrating mechanical system excited by two exciters. (November 2017) - Zhang, Xueliang; Wen, Bangchun; Zhao, Chunyu
Highlights: A roller excited by two exciters. Vibratory synchronization transmission of a roller. Synchronization of two exciters. Applications for synchronization transmission of a roller. Abstract: In present work vibratory synchronization transmission (VST) of a cylindrical roller with dry friction in a vibrating mechanical system excited by two exciters, is studied. Using the average method, the criterion of implementing synchronization of two exciters and that of ensuring VST of a roller, are achieved. The criterion of stability of the synchronous states satisfies the Routh-Hurwitz principle. The influences of the structural parameters of the system to synchronization and stability, are discussed numerically, which can be served as the theoretical foundation for engineering designs. An experiment is carried out, which approximately verify the validity of the theoretical and numerical results, as well as the feasibility of the method used. Utilizing the VST theory of a roller, some types of vibrating crushing or grinding equipments, etc., can be designed.